Novel microwave assisted sol-gel synthesis (MW-SGS) and electrochromic performance of petal like h-WO3 thin films - Kharade, Rohini R.; Patil, K. R.; Patil, P. S.; Bhosale, Popatrao N. (Materials Research Bulletin, 2012)
Use of domestic microwave oven is first time employed for chemical deposition of nanocrystalline hexagonal WO3 (h-WO3) thin films. Low cost precursors like sodium tungstate, hydrochloric acid, oxalic acid and potassium sulfate signifies cost effectiveness of this thin film fabrication route. Scanning electron microscopy images reveal formation of petal like nanodisks. A number of analytical techniques were used to characterize the WO3 petal like nanodisks, including X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX). X-ray photoelectron spectroscopy, FT-IR spectroscopy, Raman scattering spectroscopy, UV-visible spectrophotometry and cyclic voltammetry (CV). The X-ray photoelectron spectroscopic studies revealed 2.89 O/W atomic ratio. The electrical transport studies on WO3 thin films show semiconducting behavior with n-type semiconductivity. The value of determined coloration efficiency is 57.90 cm(2)/C. The mechanism of Li+ intercalation and deinercalation in h-WO3 matrix is proposed for enhanced electrochromism. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Electrochemical properties; Oxides; photoelectron spectroscopy

Enhanced electrochromic coloration in Ag nanoparticle decorated WO3 thin films - Kharade, Rohini R.; Mali, Sawanta S.; Patil, Satish P.; Patil, Kashinath R.; Gang, Myong G.; Patil, Pramod S.; Kim, Jin H.; Bhosale, Popatrao N. (Electrochimica Acta, 2013)
WO3/Ag composite thin films were prepared by microwave assisted sol-gel synthesis (MW-SGS) of WO3 followed by vacuum evaporation of Ag nanoparticles and their enhanced electrochromic coloration was investigated. The composition and morphology of WO3 thin films with different thickness of Ag layer obtained by vacuum evaporation were investigated. Distinct plasmon absorption bands of Ag nanoparticle thin films were obtained. The optical band gap energy of WO3/Ag films decreased with increasing the Ag layer thickness. The surface of these films has been examined using X-ray photoelectron spectroscopy (XPS) to gain information about the chemical states of species present at surfaces. Experimental results indicated that the conductivity of the films increased after surface modification by Ag layer. To investigate the origin of enhanced electrochromic absorption in optical properties, working electrode consisting of WO3/Ag thin film was used and observed the optical properties during electrochemical reaction. It was found that composite electrode shows enhancement in electrochromic properties in terms of optical modulation (Delta OD) and coloration efficiency (eta). (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Ag2WO4; CIE coordinates; Electrochromism; SPR; WO3/Ag composite thin films